PARADIGM AND REALITY OF LAW ENFORCEMENT IN INDONESIA - Rosdalina Bukido (Jurnal Ilmiah Al-Syir'ah, 2006)
The research on "PARADIGM AND REALITY OF LAW ENFORCEMENT IN INDONESIA" is a library research, which aims to investigate about the factors influencing failed law enforcement in Indonesia. The good law enforcement is one of the criterions success nation to increase the dignity specially in law. Law should protect all societies living anywhere. So, it can create stability and safety life of our societies. There are many functions of law. Law can make the good thing for all sectors, for example economic, politic, trade, etc. Paradigm and reality of law enforcement in Indonesia is not carried out well yet. It is caused by two factors. They are officers of law enforcement (judge, police, advocate, and public prosecutor). If they have the good morality and integrity, law enforcement can run well. The second is Indonesian legislative assembly as the makers of law. Although the makers of law are not socialization with societies directly, but the result of them can reach and cover all problems in Indonesian societies.